Biosensors in food processing, safety, and quality control - Mutlu, Mehmet (Boca Raton : CRC Press, 2011)
'This book details the latest developments in sensing technology and its application in food industry. It explores the opportunities created by the chemical and biosensensing technology and improvements performed in recent years for better food quality, better food safety, better food processing and control, and better input for food industry. The chapters in this book have been divided into three sections: basic principles of chemical and biosensing technology, biosensors for food processing and control, and biosensors for food safety'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Food -- Safety measures; Food -- Food--Quality.; Biosensors; Biosensing Techniques; Food handling; Food Contamination -- prevention & control; Food technology